Circulating nucleic acids as a new diagnostic tool - Urbanova, Marketa; Plzak, Jan; Strnad, Hynek; Betka, Jan (Cellular & molecular biology letters, 2010)
The discovery of circulating nucleic acids in the 1940s opened up new possibilities for the non-invasive detection, monitoring and screening of various human disorders. Several tumour markers that enable early cancer detection or tumour behaviour prediction have been detected in the plasma of cancer patients. Maternal plasma analysis can be used to detect certain fetal abnormalities, with the quantification of cell-free nucleic acids used to screen for several pregnancy-associated disorders. Some other applications are in transplant monitoring and graft rejection assessment, and in certain medical emergencies such as trauma and burn severity stratification. Many studies have yielded promising results in this field, but the techniques have yet to be applied in routine clinical practice. Large-scale studies using similar technologies and a broad spectrum of patients are still needed to verify the results of the various studies.
Keywords: nemoc; Disease; Nucleic Acids; Humans; nukleové kyseliny; lidé